Worries, beliefs and factors influencing perinatal COVID-19 vaccination: a cross-sectional survey of preconception, pregnant and lactating individuals - Serine Ramlawi; Katherine A. Muldoon; Sandra I. Dunn; Malia S. Q. Murphy; Alysha L. J. Dingwall-Harvey; Ruth Rennicks White; Romina Fakhraei; Shi Wu Wen; Mark C. Walker; Deshayne B. Fell; Tali Bogler; Darine El-Chaâr (BMC Public Health, 2022)
Abstract Background COVID-19 vaccines are recommended for pregnant and lactating individuals, and there is substantial evidence for their safety and effectiveness. As the pandemic continues, information on worries and beliefs surrounding perinatal COVID-19 vaccination remains important to inform efforts aimed at improving vaccine uptake. Our objectives were to assess factors associated with COVID-19 vaccination among perinatal individuals; and to explore motivational factors associated with willingness to be vaccinated among unvaccinated perinatal individuals. Methods This was a cross-sectional web-based survey of preconception, pregnant, and lactating individuals in Canada. The outcomes of interest were vaccination with at least one dose of any COVID-19 vaccine and willingness to be vaccinated among unvaccinated individuals. Sample characteristics were summarized using frequencies and percentages. The association between eight prespecified risk factors and two outcomes (vaccination status and willingness to be vaccinated) was assessed by logistic regression. Odds ratios (OR) and 95% confidence intervals (CI) were calculated for the total sample, and across perinatal sub-groups. Results Among 3446 survey respondents, there were 447 (13.0%) preconception, 1832 (53.2%) pregnant, and 1167 (42.4%) lactating. There were 1460 (42.4%) and 1982 (57.5%) who were vaccinated and unvaccinated, respectively. Factors positively associated with COVID-19 vaccine status were speaking to a healthcare provider about vaccination during the perinatal period (aOR:2.35, 95% CI:1.97–2.80) and believing that the COVID-19 vaccine is effective (aOR:1.91, 95% CI:1.46–2.48). Factors negatively associated with vaccine status included worries about fetal growth and development (aOR:0.55, 95% CI:0.43–0.70) and future child behavioral/neurodevelopmental problems (aOR:0.59, 95% CI:0.46–0.75). Among unvaccinated individuals specifically, characteristics positively associated with willingness to vaccinate were speaking to a healthcare provider (aOR:1.67, 95% CI:1.32–2.12) and believing the COVID-19 vaccine is effective (aOR:3.56, 95% CI:2.70–4.69). Factors negatively associated with willingness were concerns over infertility (aOR:0.66, 95% CI:0.49–0.88), fetal growth and development (aOR:0.33, 95% CI:0.24–0.46), and future child behavioral/neurodevelopmental problems (aOR:0.64, 95% CI:0.48–0.84). Conclusions In this Canadian perinatal population, approximately 42% reported COVID-19 vaccination. Among unvaccinated individuals, willingness to receive vaccination was high (73%). Factors enhancing vaccine willingness included discussions with healthcare providers and believing the vaccine was effective. Concerns regarding vaccine safety, particularly with respect to fetal/child development, were the greatest barriers to vaccine uptake.